Laws of the City of Johnstown, Pa., Embracing City Charter, Act of Assembly of May 23, 1889, for the Government of Cities of the Third Class, General and Special Ordinances, Rules of Select and Common Councils and Joint Sessions, at 86, General Ordinance no. 2, § 12 (1897) - (:unkn) unknown (My University, 1889)
Prohibited the concealed carrying of any pistol, razor, dirk, Bowie knife, blackjack, handy billy, or other deadly weapon. Punishable by fine of $5-50.
Keywords: CARRY - CONCEALED